The Development of Cingcoleng Cave Tourism in Tengku Leda Village, Lamba Leda District, to Support the 2030 SDGs - Meltiades Yultin; Mikael Samin; Andrinata, Andrinata (Tinta Emas Publisher, 2024)
The aim of this research is to identify supporting and inhibiting factors from an internal and external perspective in the development of Cingcoleng Cave Spiritual tourism using SWOT analysis. Data was obtained through a survey involving visitors and stakeholders at Cingcoleng Cave. SWOT analysis is carried out to assess strengths, weaknesses, opportunities and threats from internal and external perspectives. The results of this research show that in (1). Internal shows that the total strength is 2.329 compared to the weakness of 0.692. Meanwhile in (2). External opportunities have a total of 2.272 compared to threats of 0.545. based on the coordinates, it is in the area of strength and opportunity, which means that Cingcoleng Cave Spiritual tourism is in quadrant I. The strategy that must be implemented in this condition is to support an aggressive growth policy (Growth Oriented strategy). The focus of this strategy is to use the strengths of tourism to take advantage of various opportunities. The conclusions of this research indicate that the development of spiritual tourism in Cingcoleng Cave can be optimized by strengthening supporting facilities and increasing promotion through collaboration with the government and other related parties.